An analysis of the role of follicular lymphoma-associated fibroblasts to promote tumor cell viability following drug-induced apoptosis. Issue 8 (3rd August 2017) - Staiger, Annette M.; Duppel, Jasmin; Dengler, Michael A.; van der Kuip, Heiko; Vöhringer, Matthias C.; Aulitzky, Walter E.; Rosenwald, Andreas; Ott, German; Horn, Heike
Abstract: Treatment response of follicular lymphomas (FL) is highly variable. We, therefore, investigated the role of FL cancer-associated fibroblasts (CAFs) on tumor cell viability, in particular in response to treatment with cytotoxic drugs. Stromal cells outgrown from FL patients were characterized and pure CAF populations were co-cultivated with FL cells. To analyze fibroblast-mediated effects, cells in co-culture were treated with ABT-737 and Bortezomib. The adherent cell population was positive for all fibroblastic markers tested and showed increased mRNA-expression of the activation marker FAP . No effect on FL cell viability was noted when co-cultivating them with CAFs. However, stromal cells protected tumor cells from apoptosis in response to cytotoxic treatment. This might be explained by mRNA-induction of ABCC1 and ABCG2 and up-regulation of BCL2L1 in FL cells. Our finding of protective mechanisms mediated by CAFs is of pivotal impact for further studies of cytotoxic agents in FL.